THE EFFECT OF IMPLEMENTATION RELATIONSHIP MARKETING ON CUSTOMER LOYALTY IN BANK SULUT TONDANO - Ngantung, Jesika; Pangemanan, Sifrid; Worang, Frederik (Jurnal Berkala Ilmiah Efisiensi, 2015)
ABSTRACT Customer Relationship Management (CRM) is the process used to implement a relationship marketing strategy. CRM gathers market-driven data to learn more about customer needs and behaviour for the purpose of delivering added value and satisfaction to the customer. The data, in conjuction with information technology, is then used to develop stronger relationships with customers. Fundamentally, CRM is based on a number of concepts focusing on the marketplace and the consumer. This research objective is to know the effect of implementation relationship marketing on customer loyalty in Bank SULUT, Tondano. 50 respondents has used as samples. The method used is Multiple Regression Analysis. The result shows that trust, commitment, communication, conflict handling are significant influence on customer loyalty decision simultaneously. Trust and conflict handling have significant influence partially on customer loyalty. Â  Keywords: Commitment, Communication, Conflict Handling, Trust, Customer Loyalty